Influência da modulação monoaminérgica sobre comportamentos nociceptivos térmicos de Drosophila melanogaster - Bressan, Getulio Nicola (2018)
Drosophila melanogaster is an model organism that have been used to research molecular mechanisms and role of the genes and proteins involved in nociception, which have a function in detect noxious stimuli and protect the tissues of an potential damage. Molecular mechanisms that act in detecting and conducting of the nociceptive signal, involving ions channels as Transient Receptors Potential (TRP) and neurotransmitters. In D. melanogaster, TRPA1 is a receptor have activated by heat, participating in the induction of thermal nociceptive behavior as avoidance of noxious heat. The monoamines have been involved on physiological and behavioral process, for example the dopamine that supports in the control of locomotor activity and temperature sensitivity. However, little is known about the participation of serotonin in behavioral responses to heat. Therefore, we investigated whether the monoamines participate in the neuronal communication of the nociceptive pathway for the processing and response to thermal nociceptive stimuli. In this study, we research the effects of the depletion of monoamines and, selectively, oh the dopamine e serotonin, through of pharmacological manipulation, on thermal nociceptive behaviors in the D. melanogaster. Flies were treated with reserpine (10 μM, 30 μM, 100 μM and 300 μM), 3-Iodo-L-Tyrosine (5 mg and 10 mg) and p-chloro-phenylalanine (5 mg and 10 mg), then, it was subjected to behavioral tests. The reserpine reduces the thermal tolerance profile and, thus, the heat resistance of the D. melanogaster, as well as the avoidance of noxious heat. Whereas treated flies have a deficit locomotion induced by reserpine, there are flies able to execute the avoidance behavior. Also, PCPA decrease avoidance of noxious heat and heat resistance at 41º C without have impaired locomotion, suggesting that the impaired avoidance of the noxious heat is related to the reduction of the heat resistance in the D. melanogaster by this drugs. These data suggest that monoamines, particularly serotonin, are associated to the impaired avoidance of the noxious heat which could be related to the reduction of the heat resistance in the D. melanogaster.